What do Argentinean Education Laws Say about the Relationship between School and Society? - Vicente, María Eugenia (2017)
This investigation arises from a comprehensive concept of the relationship between society and school aimed at sustaining and supporting the democratization of school and the reinforcement of social ties. To this end, Argentinean education laws, regulations, circulars and rules from 1890 until the present day were analyzed. The historical review throughout the different Argentinean education laws has shown that the relation between school and society has gone through different conceptualizations.